Glioblastoma multiforme in patients over 65 – should we operate?. (12th October 2019) - Maleyko, Igor; Hall, Benjamin; Brodbelt, Andrew; Lawson, David; Jenkinson, Michael; Chavredakis, Emmanuel
Abstract: Aim: Current standard of care for glioblastoma is maximum safe resection followed by radio chemotherapy with Temozolomide. Older patients are less likely to receive the full treatment. The aim was to determine treatment and outcomes in glioblastoma patients >65 years. Methods: Single centre retrospective study from 2001–2016. Eligible patients had: (i) diagnosis of glioblastoma (ii) undergone biopsy or resection with radiotherapy ± adjuvant chemotherapy. Age at diagnosis, type of surgery, performance status, complications, adjuvant therapy and median survival (MS) were recorded. Patients were assigned to group A (age <65), B (age 65–69 years) or C (age >/= 70 years). Results: 637 patients met the eligibility criteria and 403 had complete records for analysis. Age distribution of the cohort was 17.9 – 91.6 years. In the group A (n=259), those who had undergone resection had significantly longer MS compared to biopsy: 17.2 vs 13.2 months (P<0.05 CI: 444.043 – 561.957). 70 patients developed complications. In the group B (n=79), those who had undergone resection had significantly longer MS compared to biopsy: 12.3 vs 5.1 months (P<0.05 CI: 194.354 – 335.646). 17 patients developed complications. In the group C (n=64), analysis did not show statistically significant difference (P=0.066 CI: 220.476 – 321.524). Clinically, patients who had resection had longer MS (10.5 months vs 3.5 months). Furthermore, there was no significant difference in the rate of complications between resection and biopsy (Fisher's exact test, P=0.755). Conclusion: i) Patients >65 should be treated as per the Stupp protocol ii) In patients >70 surgical resection should be considered.: